The Impact of Fundamental Development Factors on Different Income Groups: International Evidence - Alexander Stimpfle; David Stadelmann (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
We jointly analyze the causal effects of geography, trade integration, and institutional quality on different income groups for developing and developed countries from 1983 to 2012. Favorable geographic conditions tend to discriminate strongly between income groups as low incomes benefit whereas high incomes decline. Controlling for institutional quality and geography, trade integration has a negative effect which increases in absolute size and significance for higher income groups. Institutional quality strongly and positively affects all income groups, however, high income groups tend to profit relatively more than low income groups. These findings are robust for different specification tests and they are consistent over time.
Keywords: O11; O43; F43; 330